The Impact of APOE ɛ4 in Alzheimer's Disease Differs According to Age. - Kim, Jaeho; Park, Seongbeom; Yoo, Heejin; Jang, Hyemin; Kim, Yeshin; Kim, Ko Woon; Jang, Young Kyoung; Lee, Jin San; Kim, Sung Tae; Kim, Seonwoo; Lee, Jong Min; Ki, Chang-Seok; et al. (J Alzheimers Dis, 2018)
We evaluated how the impact of apolipoprotein E4 (APOE4) differs according to age in Alzheimer's disease (AD) patients. We recruited 846 AD patients and 815 cognitively normal controls and categorized into three groups with respect to their age (<65, 65-74, and ≥75 years). We evaluated the risk of AD in APOE4 carriers and compared cortical thickness and cognitive function according to APOE4 status in each age group. At the point of this study, in young (<65 years) AD, APOE4 noncarriers had the most severe frontal and perisylvian atrophy, while in old (≥75 years) AD, APOE4 carriers had the most severe medial temporal atrophy. In AD under 75 years, APOE4 noncarriers and heterozygotes showed worse performance in language, visuospatial, and frontal function compared to homozygotes, while, in old (≥75 years) AD, APOE4 homozygotes showed worse performance in memory compared to noncarriers. As the detrimental effects of APOE4 seen in older AD patients were not found in younger AD patients, we suggest that some unrevealed factors are associated with cortical atrophy and non-amnestic cognitive dysfunction in young AD with APOE4 noncarriers.
Keywords: Age Factors; Aged; Alzheimer Disease; Apolipoprotein E4; Atrophy; Brain; Case-Control Studies; Cognition; Female; Heterozygote; Humans; Magnetic Resonance Imaging; Male; Memory; Middle Aged; Republic of Korea

Trajectories of Physiological Brain Aging and Related Factors in People Aged from 20 to over-80. - Lee, Jin San; Kim, Seonwoo; Yoo, Heejin; Park, Seongbeom; Jang, Young Kyoung; Kim, Hee Jin; Kim, Ko Woon; Kim, Yeshin; Jang, Hyemin; Park, Key-Chung; Yaffe, Kristine; Yang, Jin-Ju; et al. (J Alzheimers Dis, 2018)
BACKGROUND/OBJECTIVE: In this study, we investigated a long-term trajectory of brain aging (from the 20 s to over-80) in cognitively normal (CN) individuals. We further determined whether differences in sex, education years, and apolipoprotein E ε 4 status affect age-related cortical thinning. METHODS: A total of 2,944 CN individuals who underwent high-resolution (3.0-Tesla) magnetic resonance imaging were included in this study. Cortical thickness was measured using a surface-based method. Multiple linear regression analyses were performed to evaluate age-related cortical thinning and related factors. RESULTS: Compared to those in their 20 s/30 s, participants in their 40 s showed thinning primarily in the medial and lateral frontal and inferior parietal regions, and cortical thinning occurred across most of the cortices with increasing age. Notably, the precuneus, inferior temporal and lateral occipital regions were relatively spared until later in life. Male and lower education years were associated with greater cortical thinning with distinct regional specificity. CONCLUSION: Our findings provide an important clue to understanding the mechanism of age-related cognitive decline and new strategies for preventing the acceleration of pathological brain aging.

18F-AV-1451 PET Imaging in Three Patients with Probable Cerebral Amyloid Angiopathy. - Kim, Hee Jin; Cho, Hanna; Werring, David J; Jang, Young Kyoung; Kim, Yeo Jin; Lee, Jin San; Lee, Juyoun; Jun, Soomin; Park, Seongbeom; Ryu, Young Hoon; Choi, Jae Yong; Cho, Young Seok; et al. (J Alzheimers Dis, 2017)
Cerebrovascular deposition of amyloid-β, known as cerebral amyloid angiopathy (CAA), is associated with MRI findings of lobar hemorrhage, cerebral microbleeds, and cortical superficial siderosis. Although pathological studies suggest that tau may co-localize with vascular amyloid, this has not yet been investigated in CAA in vivo. Three patients with probable CAA underwent 11C-Pittsburgh Compound B (PiB) PET or 18F-florbetaben PET to evaluate amyloid burden, and 18F-AV-1451 PET to evaluate paired helical filament tau burden. Regions that had cerebral microbleeds or cortical superficial siderosis largely overlapped with those showing increased 18F-AV-1451. Our preliminary study raised the possibility that lobar cerebral microbleeds, and cortical superficial siderosis, which are characteristic markers of vascular amyloid, may be associated with local production of paired helical filament tau.
Keywords: Aged; Aged, 80 and over; Aniline Compounds; Brain; Carbolines; Cerebral Amyloid Angiopathy; Female; Humans; Image Processing, Computer-Assisted; Male; Positron-Emission Tomography; Thiazoles